Highlighting the Effectiveness of Small and Medium Sector to Boost the Economic Development: Examining the Role of SMEs in India's Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This specific report attempted to showcasing the significance of SMEs in the economic development of India. Every small scale industry plays a huge role in the Indian economy. Apart from offering employment to crores of folks, it's the additional advantage of least capital demands. The federal government additionally provides a number of tax advantages to SSI for that purpose. In addition, they could occur in urbanized and also countryside areas. This particular paper attempted to look at the contribution of the SMEs Sector in the nation's growth and furthermore, the aspects that are needed to reinforce the SMEs sector to its constant contribution to the development of India.